2007
DOI: 10.2109/jcersj2.115.974
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Si3N4 Ceramics Sintered in Air and Nitrogen Atmosphere Furnaces

Abstract: Mass loss and mechanical properties including density and morphology of Si 3 N 4 ceramics sintered in air and in N 2 atmospheres were comparatively studied. The trends of mass loss with increasing temperature of the Si 3 N 4 sintered in air and in N 2 atmospheres were significantly different. The densities of the specimens sintered at the same temperature both in air and in N 2 atmospheres were similar. However, the mechanical properties of the materials sintered in air were lower than those sintered in N 2 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…On the other hand, the cost of β powder is usually lower than that of α powder with similar purity and grain size. In addition, some papers have suggested that β powder has better sinterability than α powder . However, these reports did not measure the differences between α and β powders in detail, especially at temperatures below 1700°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the cost of β powder is usually lower than that of α powder with similar purity and grain size. In addition, some papers have suggested that β powder has better sinterability than α powder . However, these reports did not measure the differences between α and β powders in detail, especially at temperatures below 1700°C.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some papers have suggested that b powder has better sinterability than a powder. 4,7,8 However, these reports did not measure the differences between a and b powders in detail, especially at temperatures below 1700°C. If b powder has better sinterability than a powder at lower temperatures around 1600°C and the sintered body has acceptable mechanical properties, the use of b powder would be a potential way to reduce the production cost.…”
Section: Introductionmentioning
confidence: 99%